2020
DOI: 10.1177/0268355519898322
|View full text |Cite
|
Sign up to set email alerts
|

A better inferior vena cava filter retrieval rate: A retrospective study in a single-center institution

Abstract: Purpose To determine practice patterns of inferior vena cava filters (IVCFs), retrieval rates, and reasons why retrievable-IVCFs (R-IVCFs) are kept permanent. Methods A total of 399 patients who received IVCFs at Third Hospital of Hebei Medical University from January 2017 to December 2017 were registered and retrospectively studied. Date of demographics, baseline medical history, dwell time, reasons why R-IVCFs were kept permanent, and R-IVCFs thrombus were collected. Results A total of 399 IVCFs were placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Others have found a substantial increase in retrieval rates (up to 90%) when certain follow-up strategies were implemented after filter placement. [19][20][21][22][23] These include use of multidisciplinary teams, standardized protocols, patient education, automated reminder, or referral systems and creation of dedicated VCF clinics. Such a standardized, structured follow-up program was not utilized at our institution during the study period, and despite limited data showing efficacy in increasing filter retrieval, a specific recommendation is not present in current guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have found a substantial increase in retrieval rates (up to 90%) when certain follow-up strategies were implemented after filter placement. [19][20][21][22][23] These include use of multidisciplinary teams, standardized protocols, patient education, automated reminder, or referral systems and creation of dedicated VCF clinics. Such a standardized, structured follow-up program was not utilized at our institution during the study period, and despite limited data showing efficacy in increasing filter retrieval, a specific recommendation is not present in current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have reported that the incidence of these complications increases with prolonged use of filters 13 and a decision analysis study found that the risk/benefit profile favors filter removal between 29 and 54 days. 14 Despite an increase in VCF retrieval in the United States following the 2010 FDA advisory statement [15][16][17][18] and several studies reporting retrieval rates of up to 85% following the implementation of structured follow-up programs, [19][20][21][22][23] at a national level, VCF retrieval rates remain low with an estimated average of 25 to 30% at 1 year. 13,16,18,24,25 European retrieval rates tend to be higher but vary from approximately 40 9,26 to 77% at 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…Filter thrombus, usually discovered at the time of retrieval with an incidence ranged from 6 to 81%, [15][16][17][18][19][20][21] may not be associated with a worse prognosis, [20] but it still was a common cause of IVCF retrieval failure. IVCFs with small-size thrombus (<1*1cm) could be removed using regular techniques, [15,18,22] minimal study is available on filters with massive thrombus (>1*1cm) yet. Procedures of retrieval may be directly withdrawn as thrombus within filter were confirmed by venography in the past.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Complications including filter fractures, penetration, migration, occlusions of inferior vena cava (IVC) has been emerged with the dramatic rise in permanent filter placement. [7,[9][10][11][12] Despite lots of efforts focused on improving retrieval rate in recent years, [13][14][15] some issues remain unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…The placement of the inferior vena cava (IVC) filter has been widely used in China to prevent pulmonary embolisms in patients with deep vein thrombosis (DVT), as it seems to be a safer choice than surgical plication or ligation and can be performed with minimal morbidity and mortality. 1 However, chronic indwelling IVC filters are associated with many potential risks, including penetration of the IVC, migration of the filter, infection, thrombotic events, and the potential need for lifelong anticoagulation. 2 IVC filters should be removed once the risk of pulmonary embolism has returned to baseline to prevent the significant morbidity associated with retained filters.…”
Section: Introductionmentioning
confidence: 99%